Borderless Sound, Bordered Reality: Crossfaith and the Dynamics of Transnationalism in Japanese Metalcore - Belia, Athaya Prita; Puryanti, Lina; Husain, Sarkawi B (KIRYOKU, 2025)
This paper examines the cross-border dynamics of Japanese metalcore, focusing particularly on the band Crossfaith, exploring how they navigate the complexities of global mobility, cultural identity, and transnationalism in their music. This study employs a case study approach, using document analysis as the primary method. The data then was analyzed by identifying recurring themes, patterns, and relationships. The results show that while metalcore itself is already transnational due to its use of English, Crossfaith exemplifies the creation of a "borderless" sound that transcends national boundaries. Through collaborations with international artists, performances at the Nikkosan Rinnoji Temple, and partnerships with local artists, the band manages to maintain a strong Japanese identity while appealing to a global audience. However, cross-border challenges remain, including linguistic barriers, visa restrictions, and cultural negotiations, which impact Crossfaith's international success, revealing the uneven access to global stages for non-Western artists. These challenges highlight the need for a more inclusive and accessible global music industry. This study concludes by advocating for the reduction of systemic barriers to ensure that diverse musical voices can fully participate in the global exchange of ideas, thereby enriching the cultural landscape and promoting greater cross-border collaboration in music.